10.1177/1056789514562152 (CrossRef Listing of Deleted DOIs, 2015)
Clinical electroencephalography (EEG) remains a central diagnostic tool in psychiatry. As a non-invasive, widely available and cost-effective method with high temporal resolution, EEG contributes to the detection of epileptiform activity, exclusion of organic brain dysfunction, assessment of delirium and encephalopathies, differential diagnosis of dementias, and monitoring of psychopharmacological treatments. It provides functional information that complements structural imaging and serves as an indispensable auxiliary tool in the diagnostic work up.While EEG has not demonstrated sufficient specificity as a diagnostic marker for primary psychiatric disorders, there is growing evidence supporting the predictive use of quantitative EEG features, particularly in depression. Resting-state markers, including alpha peak frequency, vigilance regulation and frontal alpha asymmetry have shown small-to-moderate effect sizes in predicting differential treatment responses to antidepressants, brain stimulation techniques, ketamine and electroconvulsive therapy. These markers operate probabilistically, shifting response likelihoods rather than determining outcomes at the individual level. Even modest predictive effects can translate into meaningful population-level improvements by reducing ineffective treatment trials and accelerating remission.In summary, electroencephalography is a valuable tool in routine clinical practice that should be part of standard diagnostic procedures. Subject to large validation studies, quantitative EEG can provide predictive instruments in precision psychiatry, enhance treatment selection and thus improve outcomes by augmenting the clinical nature of psychiatric practice.